High Order Thinking Skills (HOTS) in Learning the History of Islamic Culture Based on Neuroscience - Rahman, Khalid; Guilin, Xie; Usmaedi, Usmaedi; Fuadi, Salis Irvan; Jiao, Deng (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
One of the problems with students' skills regarding learning the history of Islamic culture in madrasas is the problem of memorization and student boredom in learning, which can be seen as the basis of this learning. Many students consider it very boring because there is a lot of memorization and reading, for this reason teachers always try to develop brain abilities (neuroscience). children in learning, where humans have different nervous system structures that can be developed, such as cognitive, affective and psychomotor aspects, and teachers also try to apply various methods in teaching so that students do not get bored in learning. In this regard, this research is intended to reveal how HOTS is used in learning the history of Islamic culture based on neuroscience. This type of research is quantitative descriptive, using Surfey and interview methods, namely interviews with teachers of the history of Islamic culture and homeroom teachers as informants in interviews about neurosins in developing students' skills in understanding learning the history of Islamic culture. In this study, researchers obtained results that students were able to apply their thinking, not just remember, restate or express thoughts without processing or observing. To assess student learning outcomes in studying the history of Islamic culture, it is necessary to improve neuroscience to find out students' skills and thinking patterns. The limitations of this research are that the research object focuses on students who already have open minds and find it a little difficult to accept suggestions and responses that differ from their thinking, as well as the process of collecting student data regarding interest in learning the history of Islamic culture also occurs problems, because The researcher hopes that future research can further develop students' skills in HOTS problems.